Kesalahan Siswa Dalam Menyelesaikan Soal Cerita: Suatu Analisis Berdasarkan Prosedur Newman Pada Materi SPLDV - Silvia Melisa Aring; Jhon R. Wenas; Anekke Pesik (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to analyze students' errors in solving mathematics problems on Systems of Linear Equations in Two Variables according to the Newman procedure. This research was conducted in class VIIIA of St. Catholic Middle School. Johanis Laikit. This type of research uses descriptive qualitative. The methods used in collecting data were written tests and interviews. The written test was given to class VIIIA students, totaling 18 students as subjects, the test questions consisted of 3 essay questions. Based on the test results, 5 students were selected based on different mistakes to be interviewed. The research results showed that from the 3 questions given, the majority of students made mistakes in answering SPLDV story questions using the Newman procedure as shown in the test results, namely errors in writing the final answer with a percentage of 74.07%, process skills errors with a percentage of 66.66%. , transformation errors with a percentage of 48.14%, understanding errors 35.18%, and reading errors 25.92%.